ANALISIS PENERAPAN LEMBAGA SERTIFIKASI HALAL DI KAWASAN ASEAN - Akhmad Rifqi Zain; Izza, M. Yusril Hafidz Nur; Azizah, Siti Nur (Program Studi Hukum Ekonomi Syariah, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2024)
ASEAN functions as a unified market and manufacturing hub, facilitating the unrestricted movement of goods, services, capital, investment, and production. This setup includes abolishing tariffs for trade among ASEAN nations, an established condition not up for negotiation, particularly for Indonesia. Implementing free trade within ASEAN raises apprehensions among the Muslim populace in Indonesia and other ASEAN nations regarding the halal status of imported products. To address these concerns, standardized terms, labels, and registration procedures are necessary for certification purposes. This study aims to compare the implementation of halal certification at halal certification bodies in ASEAN countries, especially Indonesia, Malaysia and Thailand. The study applied a comparative qualitative method by collecting primary and secondary data. Primary data were obtained from information official website of the government and halal certification bodies. Meanwhile, secondary data obtained from literature sources such as journals, articles, and books that are relevant with the research topic. Such as each country's halal standards and comparing them with technological aspects, determination procedures, legal issues, and audit methods. The analysis results show that ASEAN member countries, especially Indonesia, Malaysia and Thailand, have regulations and requirements to implement halal assurance standards. However, this difference creates confusion and hinders international trade. Abstrak ASEAN berfungsi sebagai pasar terpadu dan pusat manufaktur, yang memfasilitasi pergerakan barang, jasa, modal, investasi, dan produksi yang tidak terbatas. Salah satu peraturan yang diterapkan tarif bea masuk yang dikenakan terhadap barang-barang yang diperdagangkan di antara negara-negara anggota ASEAN. Penerapan perdagangan bebas di ASEAN menimbulkan kekhawatiran di kalangan masyarakat Muslim di Indonesia dan negara-negara ASEAN lainnya mengenai status kehalalan produk impor. Untuk mengatasi masalah ini, diperlukan persyaratan, label, dan prosedur pendaftaran yang terstandarisasi untuk sertifikasi halal. Penelitian ini bertujuan untuk menganalisis penerapan sertifikasi halal di lembaga sertifikasi halal di negara-negara ASEAN, khususnya Indonesia, Malaysia, dan Thailand. Penelitian ini menggunakan kualitatif komparatif dengan mengumpulkan data primer dan sekunder. Data primer diperoleh diperoleh dari informasi situs resmi pemerintah dan lembaga sertifikasi halal. Sementara itu, data sekunder diperoleh dari literatur seperti jurnal, artikel, dan buku-buku yang relevan dengan topik penelitian. Seperti standar halal masing-masing negara dan membandingkannya dengan aspek teknologi, prosedur penetapan, isu hukum, dan metode audit. Hasil analisis menunjukkan bahwa negara-negara anggota ASEAN, khususnya Indonesia, Malaysia dan Thailand, memiliki peraturan dan persyaratan berbeda untuk menerapkan standar jaminan halal. Namun, perbedaan ini menciptakan kebingungan dan menghambat perdagangan internasional.